Wednesday
March 22, 2017

Post a New Question

Posted by on Thursday, August 6, 2009 at 11:15am.

how would i sove this problem?

x^6 + 3x^3 + 2 = 0

  • math, - , Thursday, August 6, 2009 at 11:31am

    x^6+3x^3+2=0
    It can also be written as:
    (x^3)^2+3(x^3)+2=0...........(1)
    Let a=(x^3), then we may rewrite equation (1) as:
    a^2+3a+2=0
    or,a^2+a+2a+2=0
    or,a(a+1)+2(a+1)=0
    or,(a+1)(a+2)=0
    either,a=-1 or,a=-2
    that is (x^3)=-1 or (x^3)=-2
    Therefore, x=-1 or x=cube root of -2
    this is the solution to your equation.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question